Model of Evaluation of Accounting Information Systems Effectiveness: Multicriteria Aspect - Raupelienė, Asta (Ekonomika, 2002)
Accounting information plays the main role in the process of enterprise management. Accounting information systems (AIS) can be used to increase the efficiency or the effectiveness of the enterprises. A success of AIS usage can be ensure evaluating the effectiveness of AIS. The monographic research shows that there are many models of estimation of AIS effectiveness. Some of them can be used for qualitative or quantitative AIS analysis. Monographical research allows to make conclusion that there are no model, which can be used for complex analysis of AIS effectiveness. To reach good results, analysis of AIS effectiveness have be done from the point of view of economical, social and technical aspects. The multicriteria valuation methods, presented in this paper, can be successfully used to solve this problem. To estimate usefulness of provided model, it was made evaluation of effectiveness of three AIS Lithuanian Forest enterprises. As far as this model is open, and list of indexes can be changed without changes of model structure, it is possibility of its usage for various purposes of evaluation of AIS effectiveness.